The genesis of the administrative and legal support of defense of Ukraine - Пашинський, Володимир Йосипович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article examines the historical development of the legal support of defense of the Ukrainian state in various stages of beginning, functioning, changing forms of the state. The legal and administrative aspects of the activities on the creation of the state defense system are analyzed. Creation and development of the country as one of the most complex social phenomena of self-organization of large social groups, always accompanied by established pursuant authorities and institutions that provide self-defense against various threats, especially defense against the aggression of other countries. Defense and security of every state has always been an objective condition for the existence of democratic and sustainable development. This also applies to Ukraine, which was difficult stages of the creation of the national state, from ancient times to the present, when due to an undeclared "hybrid war" against Russia, Ukraine, is the question of the existence of the Ukrainian state. Therefore, the scientific study of patterns and characteristics of the legal defense of the Ukrainian state in various stages of emergence, operation, changes in the forms of law of the Ukrainian people, taking into account historical experience, achievements and failures in the field of defense will to avoid repetition of mistakes and rash decisions at this stage of development. At present constitution has defined the defense of Ukraine, protect its sovereignty and territorial integrity of the essential function of the state, a matter of Ukrainian people. But, these provisions are enshrined in the Constitution of independent Ukraine, the Ukrainian nation has come a long historical path of struggle for their own state and to ensure its protection and defense. The development of the defense system of the Ukrainian state, as an integral part of the state, is inextricably linked with the development and existence of various forms of state Ukrainian people. Based on the major historical periods of development of Ukrainian statehood people can identify the following main stages of formation and development of national defense: 1st - formation of Kievan Rus and stay in the Grand Duchy of Lithuania (VI-XVI centuries AD.); 2nd - Ukrainian Cossacks period from the occurrence of Zaporizhzhya Sich Cossack state to eliminate (XVI-XVIII centuries). 3 - the period of state-building processes, multi-state at the beginning of the XX century. (1917-1921 biennium.); 4 - the latest period, the system of defense of independent Ukraine (1990-2016 gg.). In the latest period of state during 1991-1996. Ukraine has a system of defense and the necessary conditions for further administrative and legal support defense functions of the state. It was created by the public authorities in the field of defense, the Armed Forces of Ukraine, the system of elements defense industry and system of laws that regulate their activities. Unfortunately, mistakes and errors in the future reform of the Armed Forces of Ukraine as a major element of defense led to losing combat capability, and they were not ready to defense, repel armed aggression. However, in the current complex military-political situation, the implementation of defense reform objectives taking into account possible past mistakes and failures and legal support main areas of defense reform as envisaged Strategic Defense Bulletin of Ukraine.